Spray drying of saffron extract-loaded coacervates by carboxymethyl cellulose/maltodextrin/saffron petal anthocyanins - Hamid Rajabi; Samineh Sedaghati; Hamidreza Farajnezhad; Seid Mahdi Jafari (Carbohydrate Polymer Technologies and Applications)
An active/dual encapsulation system was designed to enhance the stability of saffron bioactive compounds (SBCs) by incorporating saffron petal extract (SPE) as a natural antioxidant into the wall material. SBCs were encapsulated using complex coacervation of pectin (PE) and gelatin (GE), followed by spray drying (SD) with maltodextrin (MD, 15–25 g/100 mL), carboxymethyl cellulose (CMC, 0–2 g/100 mL), and SPE (0–10 mg/100 mL) as wall materials. X-ray diffraction confirmed the amorphous regions within the coacervates, indicating the formation of electrostatic interactions and hydrogen bonds. The concentration of SBCs significantly affected the polydispersity index (0.28–0.59), particle size (295–503 nm), and encapsulation efficiency (58.62–89.19%) of the coacervates. Spray-dried coacervates exhibited yields (60.23–91.20%) and encapsulation efficiencies (62.19–93.73%), both dependent on the formulation. Fourier transform infrared analysis confirmed the effective coverage of SPE by the wall materials. Stability tests showed that crocin retention was significantly enhanced by approximately 11% in the active encapsulation system (15MD/0CMC/10SPE) compared to the conventional system (23MD/2CMC/0SPE). Our findings demonstrate that this active/dual encapsulation system significantly improved the retention of SBCs, suggesting its potential use for safeguarding other bioactive components.